Improving Productivity Employ Simulation Model: A Case Study of a Steel Pipe Manufacturing Company - Qwam Alden, Arz (Anbar Journal of Engineering Sciences, 2022)
Productivity improvement in the manufacturing industry of piping is a key challenge facing manufacturers in today’s competitive markets. Improving productivity in the pipe manufacturing companies by implementing manufacturing principles that utilize simulation modeling was the purpose of this study. To improve productivity, an approach that focuses on the workstations and workforces process was suggested. The suggested approach’s goal was to increase productivity by providing customer prerequisites and leaving some products for other customers in the store. Based on the data has been gathered from the company of steel pipes, Bansal Ispat Tubes Private Limited in India, a simulation model was utilized to enhance its performance of operational. The investigation methodology consists of a simulation model, acceptable distribution, and data investigation. By simulating individual workstations and evaluating all relevant processes according to the data collected, the simulation model was built. Actual employment data were gathered from the line of manufacturing and supervisory workers, with observations carried out throughout the process of manufacturing. The used method involves videotaping of the process and interviewing workers using a video-camera. The superior continuous distributions were picked to fulfill a convenient statistical model. The results could be helps to ameliorate the manufacturing industry productivity. Furthermore, the outcomes could assist to solve the problems of scheduling in pipe manufacturing "simulating and modeling" which reveals active ways in enhancing pipe manufacturing productivity. Consequently, the findings might support well competition among companies.